SOUTH AFRICA'S EMERGING PARLIAMENTARY DIPLOMACY AND SOFT POWER (The Strategic Review for Southern Africa, 2020)
This analysis considers the emergence of South Africa's parliamentary diplomacy, or the role of Parliament on the international stage, since 1994. The early discourse both within Parliament and in academic analysis, reflects an emphasis on the role of oversight and the role of Parliament in the foreign policy decision-making process. Recognition of the role of parliamentary diplomacy has been slow to develop, although Parliament is increasingly acknowledging its role as an international actor. This has seen the development of structures and policy to support this. The value of parliamentary diplomacy as part of a country's international relations, however, remains an area in need of further deliberation. This analysis begins by unpacking the concept of parliamentary diplomacy before addressing the emerging role and value of parliamentary diplomacy for South Africa, particularly through the linkages between parliamentary diplomacy and soft power in promoting foreign policy.
Keywords: South Africa; parliamentary; diplomacy; international; Parliament; foreign policy; international actor; development; policy; international relations; soft power; decision-making; post-apartheid; Cooperation; bilateral and multilateral relations; United Nations General Assembly; multilateral organisations; Pan-African Parliament; NATO; ANC; political culture